Revitalisasi Pemikiran Ismail Raji Al-Faruqi : Strategi Baru dalam Islamisasi Pengetahuan di Abad 21 - Khairunnisa Khairunnisa; Wedra Aprison; Andy Riski Pratama (Pusat Riset dan Inovasi Nasional, 2025)
This article examines the revitalization of Ismail Raji Al-Faruqi's thought in the context of Islamic education in the 21st century, focusing on the development of new strategies for the Islamization of knowledge. Amid the challenges of globalization, technological advancements, and rapid social changes, Islamic education faces various issues that require innovative approaches. This study aims to analyze key concepts in Al-Faruqi's thought, including the importance of integrating Islamic values into curricula and teaching methodologies. Through a qualitative approach, the article also explores models of learning that can be applied in higher education institutions to create a relevant and responsive learning environment. The findings indicate that implementing Al-Faruqi's revitalization strategies can not only enhance the quality of Islamic education but also equip students with the skills and values necessary to face global challenges. Thus, Al-Faruqi's thought remains a vital foundation for the progressive and adaptive development of Islamic education.